Removal Interferences with Spectrophotometric Study for the Determination of Chromium, Vanadium and Their Application - Jassim, A. H.; Qassim, B. B.; Mansoor, A. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The species of Cr (III), Cr (VI) in biological samples and V(IV), V(V) in foods & plants samples were determined by spectrophotometric methods. Integrated spectral studies of complexes [Cr (III, VI)-DPC], [Cr (VI)-bipy], [VO-SH], [V (V)-8-HQ] which included a study of the optimum conditions for the complexes formation by the investigation of the chemical and physical variables affecting each complex formation, the nature of complexes, the preparation of calibration curves of the complexes and treated the resulted data by modern statistical methods and study the interfering species. Interferences were removed to explain the reactions thermodynamically by determining Eï‚°cell, Keq. and âˆ†G values and includes a study of separating the interfering ions from chromium and vanadium ions by using ion exchange columns. The linear ranges of determination for Cr (III), Cr (VI) and V(IV), V(V) were 0.5-8 Âµgml-1 with correlation coefficients of 0.9985 to 0.9995. The detection limit for Cr(III), Cr(VI), V(IV) and V(V) were found to be 20, 15, 50 and 100 ng.ml-1, respectively. Precision was typically better than 1.5 %, based on triplicate injections. The satisfactory recovery of 98.9 % 100.81 % for Cr (VI) could be obtained from blood and urine samples and of 99.24 % 101.09 % for V (IV) could be obtained from foods samples. The results agreed with those obtained by spectrophotometric determination with standard addition method and with certified values of standard reference samples.